Development and testing of a new electronic foot health promotion programme on nurses’ foot self-care - Stolt Minna; Katajisto Jouko; Peltonen Johanna; Suhonen Riitta; Leino-Kilpi Helena (United Kingdom, 2022)
Background
Nurses form the largest professional group in health care, and they spend most of their working day on their feet. From the perspective of work well-being, healthy feet are important to tolerate the physical demands of nursing work. However, little is known about how nurses’ foot self-care practices can be promoted with computerised interventions. The aim of this study was two-fold: to explore the preliminary effects of the electronic Foot Health Promotion Programme (FHPP) on foot self-care in nurses and to examine the usability of the programme.
Methods
A single group pretest-posttest design was used. The FHPP was targeted at nurses working in the operating theatre. The FHPP lasted for 4 weeks and focused on improving nurses’ knowledge and awareness of foot self-care through self-directed learning tasks. The primary outcome was knowledge of foot self-care. The secondary outcomes were foot health and work ability. Thirty-seven participants completed the study. The outcomes were assessed at baseline (April–June 2017) and 4 weeks (August–September 2017) after the intervention ended. The data were analysed statistically.
Results
Participants’ knowledge of foot self-care and foot health improved; however, the changes were not statistically significant. The FHPP was considered to be usable and has potential as a tool to increase knowledge of foot self-care among nurses.
Conclusions
The FHPP developed in this study is a newly developed potential tool to increase nurses’ knowledge of foot self-care. Application of the FHPP as part of occupational health care may enhance nursing personnel’s foot self-care and lower extremity health.